Recovery of an injured corticoreticular pathway via transcallosal fibers in a patient with intracerebral hemorrhage - Jang, Sung Ho (BioMed Central, 2014)
BACKGROUND: Several studies have reported on injury of the corticoreticular pathway (CRP), however, little is known about the mechanism for recovery of an injured CRP. We report on a patient with intracerebral hemorrhage (ICH) who showed recovery of an injured CRP via transcallosal fibers, which was demonstrated by diffusion tensor tractography (DTT). CASE PRESENTATION: A 67-year-old man presented with complete paralysis (Medical Research Council: 0/5) of the left extremities at the onset of a right putaminal hemorrhage. At six weeks after onset, he presented with more severe weakness of proximal joint muscles than distal joint muscles (right shoulder abductor; 2(−), finger extensor; 3(+), hip flexor; 2(+), ankle dorsiflexor; 3). Although his right hemiplegia had recovered well, he consistently showed more severe proximal weakness (right shoulder abductor; 3, finger extensor; 4, hip flexor; 3(+), ankle dorsiflexor; 4) until 16 weeks after onset. On both six- and 16-week DTTs, in the left (affected) hemisphere, the CRP showed severe narrowing with discontinuation of the anterior fibers at the corona radiata on six-week DTT, however, the discontinued anterior fibers of the CRP were connected to the right cerebral cortex via transcallosal fibers on 16-week DTT. CONCLUSION: We demonstrated recovery of an injured CRP via transcallosal fibers in a patient with ICH. We believe that this might be a mechanism for recovery of an injured CRP.